Effect of a killed whole Neospora caninum tachyzoite vaccine on the crude abortion rate of Costa Rican dairy cows under field conditions - Pérez, E. (2004)
A standard field trial was carried out to assess the effect of a commercial Neospora-vaccine based on whole killed tachyzoites (Bovilis–Neoguard, Intervet1) on the abortion rate. Eight hundred and seventy-six cows, over 2.5 months pregnant, belonging to 25 Costa Rican dairy herds, were used in the analysis. For each cow vaccinated, a cow of the same herd, breed and age category, was selected as control. The period of administration of treatments extended from June to November of 2000. The treatments were administered in two, 5 ml doses 1 month apart, the first dose given between day 75 and 90 of gestation. The incidence of abortion among all treated cows was of 16.0% (140/876). The treatment specific incidence was 11.2% (49/438) and 20.8% (91/438) for the vaccinated and the placebo group, respectively. The prevented fraction by vaccination amounted to 0.46 (95% CI: 0.26, 0.61), and the cumulative incidence ratio for the vaccinated group was 0.54. The Cox hazard ratio was 0.51(95% CI: 0.37, 0.72), meaning that the force of abortion is reduced twice in the vaccinated group. The results of this study, the first one following this type of design, shows that the killed whole Neospora caninum tachyzoite preparation had a reasonable effect on the abortion rate in Costa Rican dairy cattle. # 2004 Elsevier B.V. All rights reserved.